Factors that affect on the Event of Lung TB in Jati Kudus Health Center - Maria Ulfa1 , Windhu Purnomo2 , Rachmah Indawati2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, which can attackthe lungs and other organs. Pulmonary tuberculosis is still one of the world’s public health problems eventhough TB control efforts have been implemented in many countries since 1995. The target of the nationalpulmonary TB prevention program is eliminated in 2035 and Indonesia free from pulmonary TB in 2050.Purpose of Research, this is to find out the factors that influence the incidence of pulmonary tuberculosisin the Jati Health Center Area. This study uses secondary data taken from data from the Jati Health Centerand the analysis in this study uses the CHAID Exhaustive method. The results of this study indicate thatthe number of pulmonary tuberculosis patients with a positive smear suspicion when viewed from the typeof sufferers is mostly new cases as many as 216 people. Associated with the type of patient who came fortreatment at the Teak Health Center, all patients seeking treatment received a cure category of 99.6% whichis a new patient treatment category. So the factors that influence the incidence of pulmonary tuberculosis arethe type of patient and treatment results.